Pengaruh Tekanan Kerja dan Status Kepegawaian terhadap Kinerja Karyawan di PT Bank Tabungan Negara (BTN) KC Medan - Hilma Harmen; Adha Mahyundari; Paula Florensia Munthe; Serly Sahfitri; Nazwa Aulia Putri; Rachel Sthepanie Jovanca Nababan; Novia Christin Limbong (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze the effect of work pressure and employment status on employee performance at PT Bank Tabungan Negara (BTN) KC Medan. The research employed a quantitative method using a saturated sampling technique involving 69 outsourced employees (TAD). Data were collected through questionnaires and analyzed using multiple linear regression, t-test, F-test, and coefficient of determination. The validity test showed Pearson correlation values ranging from 0.684 to 0.840, while the reliability test showed Cronbach’s Alpha values between 0.924 and 0.940, indicating that all instruments were valid and highly reliable. Classical assumption tests confirmed that the data met the requirements of normality, linearity, multicollinearity, and heteroscedasticity. The partial test results showed that work pressure had a negative and significant effect on employee performance, while employment status had a positive and significant effect on employee performance. Simultaneously, both variables significantly affected employee performance with an Adjusted R² value of 0.642, meaning that 64.2% of employee performance variation could be explained by both variables. The company is expected to manage workloads more effectively and improve career development opportunities for outsourced employees.